2016
DOI: 10.1371/journal.pone.0156646
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Intra and Inter-Observer Reproducibility of Wrist Circumference Measurements in Obese Children and Adolescents

Abstract: In a previous study, we found that wrist circumference, in particular its bone component, was associated with insulin resistance in a population of overweight/obese children. The aim of the present study was to evaluate the intra- and inter-operator variability in wrist circumference measurement in a population of obese children and adolescents. One hundred and two (54 male and 48 female) obese children and adolescents were consecutively enrolled. In all subjects wrist circumferences were measured by two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
0
12
0
7
Order By: Relevance
“…75 More recently, wrist circumference has recently emerged as a new and highly reproducible biomarker of cardiometabolic risk. 76,77 Wrist circumference is indeed strongly and independently associated to insulin resistance, as demonstrated in a large study conducted on more than 400 children and adolescents. 49 Interestingly, the association of metabolic dysfunction with wrist circumference is kept also in overweight/obese adults at high cardiovascular risk, and it is stronger than with waist-to-hip ratio or neck circumference.…”
Section: Wrist Circumferencementioning
confidence: 75%
See 1 more Smart Citation
“…75 More recently, wrist circumference has recently emerged as a new and highly reproducible biomarker of cardiometabolic risk. 76,77 Wrist circumference is indeed strongly and independently associated to insulin resistance, as demonstrated in a large study conducted on more than 400 children and adolescents. 49 Interestingly, the association of metabolic dysfunction with wrist circumference is kept also in overweight/obese adults at high cardiovascular risk, and it is stronger than with waist-to-hip ratio or neck circumference.…”
Section: Wrist Circumferencementioning
confidence: 75%
“…49 Interestingly, the association of metabolic dysfunction with wrist circumference is kept also in overweight/obese adults at high cardiovascular risk, and it is stronger than with waist-to-hip ratio or neck circumference. 71 While this might suggest the hypothesis that the measurement of wrist circumference over the lifespan could be a nonperishable tool 76 to monitor the modification of cardiometabolic risk from childhood to adulthood, Watkins et al failed to show a significant association between wrist circumference in childhood and insulin resistance in adulthood. 52 However, a recent meta-analysis confirmed the association between wrist circumference, metabolic syndrome, and other cardiometabolic risk factors.…”
Section: Wrist Circumferencementioning
confidence: 99%
“…10 The high intra and inter-observer reproducibility demonstrated by Campagna G et al suggests that wrist circumference measurement, being safe, non-invasive and repeatable can be easily used in out-patient settings to identify youths with increased risk of insulin-resistance. 15 This can avoid testing the entire population of overweight or obese children for insulin resistance parameters. They found that wrist circumference, in particular its bone component, is highly correlated with measures of insulin-resistance in a population of overweight/obese children and adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…13 The Lister tubercle, a dorsal tubercle of the radius, can be easily palpated at the dorsal aspect of the radius around the level of the ulna head, about 1 cm proximal to the radio carpal joint space. [14][15][16][17] A tension-gated tape measure was used to ensure equivalent tape pressure between subjects. Wrist circumference was measured to the nearest 0.1 cm.…”
Section: Data Collection Methodsmentioning
confidence: 99%
“…WC is another simple anthropometric measurement, which has a safe and non-invasive method with appropriate intra-and inter-operator reliability (40). In addition, it is related to skeletal frame size, and is not affected by body fat variations (40).…”
Section: Discussionmentioning
confidence: 99%